ETNOBOTANI TANAMAN DI PEKARANGAN RUMAH MASYARAKAT KAMPUNG KWEEL DISTRIK ELIKOBEL KABUPATEN MERAUKE - maya sari rupang; Mani Yusuf; Anwar Anwar; Yosehi Mekiuw; Wa Ode Asryanti Wida Malesi; Abdul Rizal (JURNAL AGRIMENT, 2022)
Yard land is used by the community to grow crops to meet their daily needs. This research is to find out the species of garden plants used by the people of Kampung Kweel. Data collection to determine plant species in the yards of community houses was carried out using interviews and documentation methods. Identification and inventory are carried out based on local names, scientific names, family names, and plant parts used. Data were analyzed using qualitative analysis by describing the results of interviews and surveys of the plants found. Meanwhile, quantitative analysis was carried out by presenting the part of the plant used. The results showed that there were 21 species of plants in the yard of Kampung Kweel with different benefits. The part of the plant that was used with the highest percentage was obtained from the fruit of 37.50%, followed by leaves of 28.13%, stems and tubers of 12.50%, rhizomes of 6.25% and flowers of 3.13%